2015
DOI: 10.5751/es-07243-200146
|View full text |Cite
|
Sign up to set email alerts
|

Educating for resilience in the North: building a toolbox for teachers

Abstract: ABSTRACT. Communities at far northern latitudes must respond rapidly to the many complex problems that are arising from changing climate. An emerging body of theoretical and empirical work has explored the role that education plays in enhancing the resilience and adaptability of social-ecological systems. To foster effective, local, and timely responses of high-latitude communities to climate-driven social-ecological change, educators need access to successful and efficient teaching tools to foster resilience-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 99 publications
(113 reference statements)
0
17
0
5
Order By: Relevance
“…It was still many places which were needed to visit as students learning resources. (Spellman, 2015) "Actually from the government program if it viewed from K-13, it has entered in environmental activities and it is not separate"(KA. 08-02-2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was still many places which were needed to visit as students learning resources. (Spellman, 2015) "Actually from the government program if it viewed from K-13, it has entered in environmental activities and it is not separate"(KA. 08-02-2016).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, our analyses might be limited to comprehensively unveiling the participants' learning during and after the field trip program, which remains a limitation of this study. Less is known about methods to evaluate the learning provided by social-ecological system education [11]. Recently, Milfont and Duckitt [51] invented the Environmental Attitude Inventory (EAI) that can determine the multi-dimensional aspects of environmental attitudes; however, it is limitedly applied due to the complicated questionnaire.…”
Section: Constructive Learning and Education For Building A Social-ecmentioning
confidence: 99%
“…However, our case study indicated that this understanding is not widely spread within the Transition Movement (Appendix 5:1). At the same time, complexity thinking has been identified as a key aspect of enhancing resilience thinking in the governance of socialecological systems , and systems thinking as one of the teaching practices that can increase resilience (Spellman 2015). An integrated approach to applying resilience thinking could foster this understanding by combining the Resilience http://www.ecologyandsociety.org/vol22/iss1/art28/ Assessment's complexity theory, e.g., the adaptive cycle and panarchy (Gunderson and Holling 2002), with the Transition Movement's pedagogical exercises on resilience and systems thinking.…”
Section: Synergies In Fostering Complex Systems Understandingmentioning
confidence: 99%